Translating Poetry: Possibility or Impossibility? (Journal of the College of Education for Women, 2019)
Translating poetry is considered one of the most complicated types of translations. Itencounters many difficulties, the most important of which is the question of possibility orimpossibility of translating poetry. So, it is better to start by asking the following question: isthe translation of poetry possible? Or is it impossible? It is definitely a rhetorical questionbecause translation is as old as the presence of translated texts, which fills the shelves oflibraries. One can ask despite these difficulties, who would discourage people of the worldfrom translating poetry merely because it is fundamentally impossible? (Mann, 1970: 211)The present paper will elaborate, in more detail, upon the necessary traits of translation andpoetry, and will seek the intellectual attitudes that deal with the issue of the possibility orimpossibility of translating poetry by representing the views with or against the translation ofpoetry, as well as shedding some light on the problematic issues to be tackled in this arena.Finally, it will adopt a certain assessment model of a selection of texts that show theimpossibility of translating poetry. It is worth mentioning that the idea of writing a paper onthis theme is the outcome of the researcher's work with poets. The researcher have edited andtranslated a book from English into Arabic entitled On Poetry and Translating Poetry(2012, Beirut: Al-Jamal Publishing House). She faced many problems that urged her to writethis paper, among which, for instance, are the phonological, linguistic and cultural ones. Thepaper will adopt translations taken from this book to show these difficulties.